2016
DOI: 10.1142/s0219091516500247
|View full text |Cite
|
Sign up to set email alerts
|

Do Well-Financial Holding Company Organized Banks in Taiwan Take More Risk?

Abstract: This paper employs panel data regression analysis to explore the measurable differences in risk-capitalization relationship between FHC and non-FHC organized Banks. The main contribution of this paper is in explaining some rethinking which shows the business of FHCBs take more risk than that of NFHCBs, and high degree of capitalization is negatively associated with asset risk and has higher interest rate spread increased bank’s asset risk in FHCBs only. It obviously has its strong anti-incentives domination fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…Although, bank size and loan to deposit ratio were shown to be negatively related with NPLs of the sample banks that is consistent with the findings of Hu et al (2004);Ćurak et al (2013) and Lai et al (2016), the relationship, however, was not significant. Lastly, our findings do not support evidence that macroeconomic factors influence NPLs as found by Messai and Jouini (2003), Bayar (2019), Kjosevski et al (2019), Alshebmi et al (2020) and many more.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Although, bank size and loan to deposit ratio were shown to be negatively related with NPLs of the sample banks that is consistent with the findings of Hu et al (2004);Ćurak et al (2013) and Lai et al (2016), the relationship, however, was not significant. Lastly, our findings do not support evidence that macroeconomic factors influence NPLs as found by Messai and Jouini (2003), Bayar (2019), Kjosevski et al (2019), Alshebmi et al (2020) and many more.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Kao et al [12] argued that increasing the size and scope of financial products does not necessarily improve the performance of banks. Lai et al [13] found that non-FHC banks have higher loan ratios, which means smaller banks are more capable of generating profits. Cheng et al [14] claimed that non-FHC banks are more capable of increasing cost efficiency than FHC banks because of their awareness of firm expenditure and desire to diversify financial products.…”
mentioning
confidence: 99%